Fruit Peel Powder as Natural Antioxidant and Reinforcing Bio-Filler in Natural Rubber Latex Gloves: Cases of Mangosteen, Pomelo and Durian - Arkarapol Thumwong; Jitsuna Darachai; Nuatawan Thamrongsiripak; Shinji Tokonami; Tetsuo Ishikawa; Kiadtisak Saenboonruang (MDPI AG, 2023)
As the world is facing rapid increases in agricultural wastes that greatly affect global health, the environment, and economies, this work aims to alleviate such issues by introducing simple uses of waste fruit peel powder (FPP) derived from mangosteen (MPP), pomelo (PPP), or durian (DPP), as dual natural antioxidants and reinforcing bio-fillers in natural rubber latex (NRL) gloves. A thorough investigation was undertaken of the relevant characteristics for both FPP (morphological, functional groups, particle sizes, and thermals stability) and NRL gloves (morphological, functional groups, density, color, thermal stability, and mechanical properties-both before and after thermal/25 kGy gamma aging). The results indicated that the initial addition (2-4 parts per hundred parts of rubber by weight; phr) of FPP to NRL composites generally enhanced the strength and elongation at the break of the specimens, with the levels of the improvement varying depending on the type and content of FPPs. In addition to the reinforcing effects, the FPP also offered natural antioxidant properties, evidenced by higher values of aging coefficients for all FPP/NRL gloves under either thermal or 25 kGy gamma aging than those of pristine NRL. Furthermore, by comparing the tensile strength and elongation at break of the developed FPP/NRL gloves with the requirements for medical examination latex gloves according to ASTM D3578-05, the recommended FPP contents for actual glove production were 2-4 phr for MPP, 4 phr for PPP, and 2 phr for DPP. Consequently, based on the overall outcomes, the FPPs of interest showed promising potential for utilization as simultaneous natural antioxidants and reinforcing bio-fillers in NRL gloves, which would not only enhance the strength and ability of the gloves to resist oxidative degradation from heat and gamma irradiation but also increase their economical value as well as reducing the amounts of the investigated wastes.